The Use of Information and Communication Technology and Social Media to Improve Change Planning and Effectiveness in Teaching and Learning Among Ghanaian Graduate Students - Boateng, John Kwame; Asare Tutu, Raymond; Boateng, Joyce (Journal of Interdisciplinary Studies in Education, 2021)
This study examined constituents of students’ perceptions on student-instructor, student-student and student-content interactions in a graduate course at University of Ghana. A survey (n=77) and focus group discussion (n=6), were employed in a Research Methods class at the University. Main constituents of students’ perceptions of and preference to student-student, student-instructor and student-content interactions were (1) perceived utility of course management systems and their ease of use; (2) perceived importance of social media and convenient access to instructors; and (3) perceived efficacy of the role of course multi-media and timely receipt of course information. The study concluded that, Sakai is a useful intermediary facilitating feedback provision, effective planning and promoting change in the design, development and delivery of graduate education.